2016
DOI: 10.3390/foods5010020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Mineral Concentration for the Geographic Identification of Garlic Samples from Sicily (Italy), Tunisia and Spain

Abstract: We performed a statistical analysis of the concentration of mineral elements, by means of inductively coupled plasma mass spectrometry (ICP-MS), in different varieties of garlic from Spain, Tunisia, and Italy. Nubia Red Garlic (Sicily) is one of the most known Italian varieties that belongs to traditional Italian food products (P.A.T.) of the Ministry of Agriculture, Food, and Forestry. The obtained results suggest that the concentrations of the considered elements may serve as geographical indicators for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Apart from the differences between the genotypes from different growing areas, there were also differences between the ecotypes from the same region. According to Vadalà et al [25] mineral composition of garlic bulbs could be used as a means for origin discrimination between samples of different growing areas in Spain, Tunisia and Italy. Hacıseferoğulları et al [24] and Akinwande and Olatunde [26] have also reported significant amounts of K in garlic bulbs, while Mg, Na and Ca were also detected in considerable amounts.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the differences between the genotypes from different growing areas, there were also differences between the ecotypes from the same region. According to Vadalà et al [25] mineral composition of garlic bulbs could be used as a means for origin discrimination between samples of different growing areas in Spain, Tunisia and Italy. Hacıseferoğulları et al [24] and Akinwande and Olatunde [26] have also reported significant amounts of K in garlic bulbs, while Mg, Na and Ca were also detected in considerable amounts.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The identification of geographic provenience of food represents, first, a current and global issue for consumers, who show increasing interest in the traceability of food supply, and, second, an important quality parameter to bring about the protected denomination of origin for some foods. 20 Several techniques are applied to the study of food quality and traceability, such as foodomic methods, chromatographic and spectroscopic techniques, among others, [21][22][23][24][25] but multi-elemental analysis (MEA) is the most commonly used. 26 MEA, in fact, represents an effective analytical approach to individuate the geographical origin of food products but also to analyze some different environmental and geological features, such as soil type, pH, porosity, humidity, rainfall and temperature, able to influence the element profile and provide the greatest discriminating power.…”
Section: Introductionmentioning
confidence: 99%
“…The PCA was to use a few indicators to replace and reflect more original information (Mottese et al, 2017). LDA is based on some indicators observed to classify the object, and the discriminant function developed is employed to classify the unknown samples (Vadala et al, 2016). LDA process: all samples were divided into calibration set and validation set.…”
Section: Discussionmentioning
confidence: 99%